Audit and Revision in Lithuania in 1919–1940 and After 1990 - Vaivadienė, Daina (Ekonomika, 2000)
Documents and laws representing history of audit development in 1919–1940 and after 1990 are analysed using analysis, synthesis, comparison, induction, deduction methods. Audit origin, differences and similarities of revision and audit functions, organisation, personnel competence is presented. The enables to understand the purposes and development perspectives of audit and revision. The co-operatives societies and the revision services carried out the external control. Revision commission inside the co-operative in 1919–1940 fulfilled the internal control. Revision commission works nowadays also. The internal audit committee is beginning to be formed instead of it. Independent audit firms and Revision department nowadays fulfil the external control. The main problem today is the separation of the functions of reviser, external and internal auditors.